Răspuns :
[tex]( \frac{5}{4} - 0,5) ^{2} : 0,75 - \frac{1}{2} = \frac{x}{4} \\ \\ \frac{ (\frac{3}{4}) ^{2} }{0,75} - \frac{1}{2} = \frac{x}{4} \\ \\ \frac{ \frac{ {3}^{2} }{ {4}^{2} } }{0,75} - \frac{1}{2} = \frac{x}{4} \\ \\ \frac{ \frac{9}{16} }{0,75} - \frac{1}{2} = \frac{x}{4} \\ \\ 0,75 - \frac{1}{2} = \frac{x}{4} \\ \\ 0,25 = \frac{x}{4} \\ \\ 0,25 \times 4 = x \\ \\ x = 1 [/tex]
[tex] \it \left(\dfrac{5}{4} -0,5\right)^2:0,75-\dfrac{1}{2} =\dfrac{x}{4} \Leftrightarrow \left(\dfrac{5}{4}-\dfrac{2}{4}\right)^2:\dfrac{3}{4} -\dfrac{1}{2} =\dfrac{x}{4} \Leftrightarrow
\\ \\ \\
\Leftrightarrow \left(\dfrac{3}{4}\right)^2 \cdot\dfrac{4}{3} -\dfrac{1}{2} =\dfrac{x}{4} \Leftrightarrow \dfrac{3}{4} \cdot\dfrac{3}{4} \cdot\dfrac{4}{3} -\dfrac{1}{2} =\dfrac{x}{4} \Leftrightarrow \dfrac{3}{4} -\dfrac{^{2)}1}{\ 2} =\dfrac{x}{4} \Leftrightarrow [/tex]
[tex] \it \dfrac{3}{4} -\dfrac{2}{4} =\dfrac{x}{4} \Leftrightarrow \dfrac{1}{4} =\dfrac{x}{4} \Leftrightarrow x = 1. [/tex]